The prevalence of traumatic dental injuries to permanent anterior teeth and its relation with predisposing risk factors among 8-13 years school children of Vadodara city: An epidemiological study - M C Patel; S G Sujan (Wolters Kluwer Medknow Publications, 2012)
Background and objective: dental trauma is an irreversible pathology that after occurrence is characterized by life-long debilitating effects. The objectives of this study were to measure the prevalence of anterior teeth fracture and their association with predisposing factors such as lip coverage, molar relationship, overjet, and variables such as age, sex, cause, and place of trauma. Materials and Methods: an epidemiological cross-sectional study was carried out among 3708 school children aged 8-13 years in the Vadodara city. All children completed a questionnaire related to history of trauma to their anterior teeth after which they were examined for lip competence, Angle's molar relationship amount of overjet and nature of trauma sustained. The results were statistically analyzed using the prevalence test, Chi-square test, and Mantel-Haenszel Common Odds Ratio. Results: the prevalence of traumatic injuries was 8.79% and the ratio of boys: girl's was 1.28:1. Inadequate lip coverage group sustained about five times more injuries than the adequate lip coverage group (P = 0.000, OR= 5.407). The maximum traumatic injuries were seen in children having Angle Class II Div 1 molar relationship and/or overjet greater than 5.5 mm and was statistically significant (P<0.05). Maximum number of injuries occurred at 9 years of age. The most predominant injuries were enamel fractures, the most common place for occurrence was home and fall against object, the most frequent cause. Conclusion: the prevalence of dental injuries in the Vadodara city is high and it has a great potential to be considered as an emerging public health problem.